Avaliação do risco de incêndio de edificações em conformidade com a legislação de prevenção e proteção contra incêndio do estado do Rio Grande do Sul através do método de Gretener: um estudo em uma IES. - Favarin, Eleusa de Vasconcellos (2015)
Due to the tragedy that occurred in the city of Santa Maria, the fire of the nightclub Kiss, emerged in the state of Rio Grande do Sul the need for a more current, more rigid and more effective legislation for prevention and fire protection. This paper aims to identify the index of fire safety in buildings of an institution of higher education that are in accordance with current legislation prevention and fire protection in the state of Rio Grande do Sul. The method the risk assessment of fire used this study is the method Gretener. The technique that will be used in this exploratory research is the case study, applied to buildings of an institution of higher education with Plan for the Prevention and Protection against fires (PPCI) developed under state law and distinct classifications as the occupation. The findings indicated that all buildings analyzed present an acceptable fire safety index according to the Gretener method and does not require any intervention on the safety measures against fire. Therefore the state law stick with your goal is, among others, establish a set of effective measures of prevention and fire protection for buildings.